Urban form evolution and transformation of traditional water towns based on space syntax and GIS: evidence from ancient Wenzhou city (16th to the 20th century) - Huang, Yuhao; Shi, Zehui; Chen, Yile; Zhou, Kai; Ying, Ziyi; Zheng, Liang; Yang, Shuai (Frontiers in Earth Science, 2025)
The traditional form of a water town is the result of a combination of urban history, culture, and spatial structure. This study digitized historical maps of ancient Wenzhou City from four developmental periods (1566, 1765, 1876, and 1949); employed space syntax to compute the integration, choice, and intelligibility of the road and water networks; and categorized and annotated the architecturally functional attributes of the ancient city using geographic information systems software. The findings indicate that (1) ancient Wenzhou City’s morphological development gradually transitioned from a singular, enclosed urban configuration to a decentralized, open urban framework, with urban functions evolving from defensive to economic and multipurpose. (2) The street structure and the water network axis in the ancient city reflected three stages of urban morphological evolution, namely, the defense-oriented stage (1566), the commercial expansion stage (1765–1876), and the modernization transformation stage (1949). (3) The architecturally functional attributes of the ancient city of Wenzhou evolved from being defense dominated to coexisting commercial, residential, industrial and other functional uses. This study provides a systematic research framework for the spatial structure evolutionary law and functional layout characteristics of ancient water towns and provides a reference case for planning strategies and the protection of ancient water towns.